Octahedral copper(ii)-diimine complexes of triethylenetetramine: effect of stereochemical fluxionality and ligand hydrophobicity on CuII/CuI redox, DNA binding and cleavage, cytotoxicity and apoptosis-inducing ability. Issue 24 (8th June 2020) - Sharma, Mitu; Ganeshpandian, Mani; Majumder, Munmi; Tamilarasan, Ajaykamal; Sharma, Mukesh; Mukhopadhyay, Rupak; Islam, Nashreen S.; Palaniandavar, Mallayan
Abstract : Stereochemical fluxionality of octahedral [Cu(trien)(diimine)] 2+ complexes determines the Cu II /Cu I redox potential, DNA binding affinity, ROS generation, cytotoxicity and apoptosis-inducing ability. Abstract : Octahedral copper(ii ) complexes of the type [Cu(trien)(diimine)](ClO4 )2 (1–4 ), where trien is triethylenetetramine and diimine is 2, 2′-bipyridine (1 ), 1, 10-phenanthroline (2 ), 5, 6-dimethyl-1, 10-phenanthroline (3 ), and 3, 4, 7, 8-tetramethyl-1, 10-phenanthroline (4 ), have been isolated. Single crystal X-ray structures of 1 and 2 reveal that the coordination geometry around Cu(ii ) is tetragonally distorted octahedral. The stereochemical fluxionality of the complexes illustrates the observed trend in Cu II /Cu I redox potentials and DNA binding affinity ( K b : 1, 0.030 ± 0.002 < 2, 0.66 ± 0.01 < 3, 1.63 ± 0.10 < 4, 2.27± 0.20 × 10 5 M −1 ), determined using absorption spectral titration. All complexes effect oxidative DNA cleavage more efficiently than hydrolytic DNA cleavage. The bpy complex 1 with stereochemical fluxionality lower than its phen analogue 2 shows a higher cytotoxicity against both A549 lung (IC50, 3.3 μM) and MCF-7 human breast (IC50, 3.9 μM) cancer cells, and induces the generation of the highest amount of ROS in A549 cells. Complex 3 with a higher stereochemical fluxionality and higher ligand hydrophobicity exhibits a higher DNA binding and cleavage ability and higher cytotoxicity (IC50, 2.1 μM) towards MCF-7 cells. Complex 4 with a still higher stereochemical fluxionality displays the highest DNA binding and cleavage ability but a lower cytotoxicity towards both A549 and MCF-7 cell lines due to its tendency to form a five-coordinated complex with the uncoordinated amine group. Annexin V.Cy3 staining and immunoblot analysis demonstrate the mechanism of cell death caused by 1 and 2 . The finding of the up-regulation of the pro-apoptotic Bax protein and down-regulation of PARP protein in western blot analysis confirms the induction of apoptosis by these complexes.